2018
DOI: 10.1002/adts.201800165
|View full text |Cite
|
Sign up to set email alerts
|

2D Nitrogen‐Containing Carbon Material C5N as Potential Host Material for Lithium Polysulfides: A First‐Principles Study

Abstract: Two-dimensional (2D) materials are identified to be efficient in many applications. In this work, a novel 2D nitrogen-containing carbon material, C 5 N, is theoretically designed through structure changes in atomic scale, that is, introducing V C -V N bivacancy defects along lines in perfect C 3 N monolayer. C 5 N monolayer is verified to be chemically, mechanically, dynamically, and thermodynamically stable based on cohesive energy, elastic constants, phonon spectrum, and molecular dynamics calculations. C 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Reproduced with permission from Ref. [ 27 ]. Copyright permissions from Elsevier, Royal Society of Chemistry and Wiley–VCH.…”
Section: Cnbmsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reproduced with permission from Ref. [ 27 ]. Copyright permissions from Elsevier, Royal Society of Chemistry and Wiley–VCH.…”
Section: Cnbmsmentioning
confidence: 99%
“…Also, analysis of the band structure shows that the Fermi level is located below the valence-band maximum, which suggests it will be metallic and display superior conductivity than other carbon nitrides (Fig. 4 m, n) [ 27 ].…”
Section: Cnbmsmentioning
confidence: 99%
See 2 more Smart Citations
“…[27] Moreover, theoretical studies suggested that carbon-based materials (such as C 3 B, C 2 N, C 3 N 4 , and C 5 N) exhibit outstanding anchoring performance for lithium polysulfides with strong adsorption energies that can suppress the shuttling effect. [18,28,29] And a porous carbon host materials are favorable for maintaining good electrochemical performance and high sulfur loading. [30] In this regard, a porous 2D graphdiyne (GDY) [31,32] has attracted tremendous interest because of its unique structural, physical, and chemical properties, and they have been predicted to have promising applications in various fields such as catalysis, energy storage, and nanoelectronics.…”
Section: Introductionmentioning
confidence: 99%